KAJIAN PERANAN ORIENTASI WIRAUSAHA DAN INOVASI PRODUK TERHADAP KEBERHASILAN USAHA UMKM DI KOTA MALANG - Ita Rifiani Permatasari; Ayu Sulasari (Politeknik Negeri Malang, 2019)
This study aims to examine descriptively the role of factors in business success, namely the Entrepreneurial Orientation and Product Innovation variables for Business Success, with the subject of Micro, Small and Medium Enterprises (UMKM) focusing on the culinary field in Malang. This study involved 100 UMKM engaged in the Culinary field in Malang. Research analysis using quantitative descriptive methods, to analyze the role of the Entrepreneurial Orientation and Product Innovation variables on business success. The results showed that the majority of Culinary UMKM owners were young people, with a maximum age of 35 years totaling 66 people (66%), with high school education, 99 people as a graduate or 99%, meaning that young people with higher education had no doubt. choose to become an entrepreneur as a choice of profession. The description of the entrepreneurial orientation illustrates that most of the culinary UMKM, already have a good entrepreneurial orientation. The results of the assessment of product innovation variables illustrate that culinary UMKM do have a good understanding of the importance of product innovation. The assessment results of business success illustrate that the majority of culinary UMKM entrepreneurs believe that the ongoing business already has quite high success.